Profiling of Measles-Specific Humoral Immunity in Individuals Following Two Doses of MMR Vaccine Using Proteome Microarrays - Haralambieva, Iana H. (Viruses, 2015)
Introduction: Comprehensive evaluation of measles-specific humoral immunity after vaccination is important for determining new and/or additional correlates of vaccine immunogenicity and efficacy. Methods: We used a novel proteome microarray technology and statistical modeling to identify factors and models associated with measles-specific functional protective immunity in 150 measles vaccine recipients representing the extremes of neutralizing antibody response after two vaccine doses. Results: Our findings demonstrate a high seroprevalence of antibodies directed to the measles virus (MV) phosphoprotein (P), nucleoprotein (N), as well as antibodies to the large polymerase (L) protein (fragment 1234 to 1900 AA). Antibodies to these proteins, in addition to anti-F antibodies (and, to a lesser extent, anti-H antibodies), were correlated with neutralizing antibody titer and/or were associated with and predictive of neutralizing antibody response. Conclusion: Our results identify antibodies to specific measles virus proteins and statistical models for monitoring and assessment of measles-specific functional protective immunity in vaccinated individuals.